A new hyper-viscoelastic model for investigating rate dependent mechanical behavior of dual cross link self-healing hydrogel. (August 2019) - Ghorbanoghli, A.; Narooei, K.
Highlights: Hyper-viscoelastic constitutive modeling based on Prony series. Number of cycles for preconditioning. Prediction of healing time. Dependence of energy dissipation on loading-unloading rate. Abstract: Self-healing hydrogels have been considered as an appropriate material for the biomechanical applications. Time-dependency and hyperelasticity are the significant mechanical behavior of these materials. In this research, a new hyperelastic strain energy function based on the polynomial-logarithmic terms was generalized to hyper-viscoelastic model for investigating the mechanical behavior of the dual cross self-healing hydrogel. The model parameters were determined by fitting with the experimental results of Long et al. and the material stability of the model in the pure shear and balance biaxial modes were investigated. It was observed the minimum strain rate for considering the rate dependent behavior is 0.003/s and below of this threshold the rate-dependent behavior could be neglected. The relaxation behavior of the hydrogel was simulated and results represented a good agreement with the experimental results. By ensuring the material stability, the cyclic loading was simulated and it was observed after three cycles the preconditioned state could be reached. Moreover, it was observed the energy dissipation depends on the loading-unloading rates. The hyper-viscoelastic model was used to simulate the healing process in the ABAQUS software using the VUMAT user subroutine. It was seen at least 300 s should be considered between the load/unload cycles to observe the healing phenomenon.